Different repetitions: Anthropological engagements with figures of return, recurrence and redundancy. Issue 2 (15th March 2019) - Bandak, Andreas; Coleman, Simon
ABSTRACT: It is a central contention of this special issue that an anthropological engagement with repetition has the capacity to open up fertile fields of comparative ethnographic and historical work. In this introduction, we link our approach to past anthropological and philosophical works, connecting for instance to discussions of historiography, rhythm, scale, and the characterization of experience. We move on to consider the present and future uses of the concept of repetition, providing five 'dimensions' that we consider helpful in exploring its nuances as well as its potentialities. These dimensions we designate as matters of production, medium, anticipation, consequence and scale. Each might be recognized within the discourse of informants or ethnographers or both. What they are intended to do is to provide an operational framework through which to anatomize processes of repetition as observable in whichever 'field' we are investigating.